Phaeohyphomycosis in Transplant Patients - Sanjay G. Revankar (Journal of Fungi, 2015)
Phaeohyphomycosis is caused by a large, heterogenous group of darkly pigmented fungi. The presence of melanin in their cell walls is characteristic, and is likely an important virulence factor. These infections are being increasingly seen in a variety of clinical syndromes in both immunocompromised and normal individuals. Transplant patients are especially at risk due their prolonged immunosuppression. There are no specific diagnostic tests for these fungi, though the Fontana-Masson stain is relatively specific in tissue. They are generally seen in a worldwide distribution, though a few species are only found in specific geographic regions. Management of these infections is not standardized due to lack of clinical trials, though recommendations are available based on clinical experience from case reports and series and animal models. Superficial infections may be treated without systemic therapy. Central nervous system infections are unique in that they often affect otherwise normal individuals, and are difficult to treat. Disseminated infections carry a high mortality despite aggressive therapy, usually with multiple antifungal drugs. Considerable work is needed to determine optimal diagnostic and treatment strategies for these infections.